Utilization of Space Based on Renewable Energy in the New City of Moncongloe-Pattalassang Metropolitan Mamminasata, Indonesia - Surya, Batara; Syafri, Syafri; Thamrin, Rahmawati; Sariman, Syahrul; Hernita, Hernita; Salim, Agus; Nasrullah, Nasrullah (International Journal of Energy Economics and Policy, 2024)
Allocation of space in the development of new city areas for the needs of socio-economic activities contributes to the complexity of land use and environmental degradation. This study aims to: (1) Analyze the effect of space utilization allocation, activity systems, and population mobility on the increase in energy demand for the new city of Moncongloe-Pattalasang; (2) Analyze the direct and indirect effects of activity systems, changes in land use, allocation of space use, on the need for renewable energy, and improving the environmental quality of new city areas; and (3) Formulate a model of space utilization based on renewable energy and the sustainability of new city development. This study uses a qualitative and quantitative approach. Data obtained through observation, surveys, in-depth interviews, and documentation. The results of the study show that the allocation of space utilization coupled with the use of renewable energy contributes to improving the environmental quality of the new city of Moncongloe-Pattalassang. The allocation of space utilization, activity systems, and population mobility explains that 97.61% of the energy needs of the new city of Moncongloe-Pattalassang. Furthermore, the influence of the total activity system, changes in land use, and allocation of space use on renewable energy needs contributed 60.58% and the direct influence of renewable energy demand on improving the environmental quality of the new city of Moncongloe-Pattalassang was 67.73%. This study recommends the use of renewable energy to support social activity functions towards improving environmental quality and the sustainability of the development of the new city area Moncongloe-Pattalassang.